Fishery, systematics and stock dynamics of billfishes landed along the Indian coast: Stock dynamics of billfishes - S. Surya; R. Prathibha; E. M. Abdusammad; T. L. Asha; B. Santhosh; B. B. Nayak; N. S. Jeena; K. G. Mini; Shubhadeep Ghosh; J. H. Kingsly; P. Abdul Azeez; C. Anulekshmi; et al. (Indian Journal of Fisheries, 2023)
Sailfishes, marlins, spearfishes and swordfishes commonly referred to as billfishes are highlymigratory species, with a worldwide distribution in tropical and subtropical oceans. Thelandings of billfishes along the Indian coast registered an increasing trend with an estimatedlanding of 14,759 t in 2019. Kerala (41%) contributed the maximum followed by Tamil Nadu(28%), Andhra Pradesh (18%), Gujarat (8%) and Maharashtra (2%) to the total billfish landingsduring the last decade. Mechanised gillnetter cum hook and line was the major gear landingbillfishes. The major species landed during 2012-2019 were Istiophorus platypterus (52.2%),Istiompax indica (21.1%), Makaira nigricans (7.3%), Xiphias gladius (17.2%) and Kajikia audax(2.3%). Four of these species could be easily distinguished by COI barcodes but, the stripedmarlin, K. audax showed high sequence similarity with K. albida and cannot be distinguishedby barcodes alone. Control region (889 bp) provided a better phylogenetic signal, consistentwith that of the whole mitochondrial genome topology. The stock status plots of billfishesdepicted that, all the species were in the developing and exploited phase. Growth, mortalityand exploitation rates estimated for four billfishes indicated that the present fishing ratesand biomass levels are at safe levels and there is considerable scope for enhancing theirfishery.Keywords:CO1 barcodes, Exploitation rate, Large pelagics,Life history, Stock status plots